THE INFLUENCE OF SELF-EFFICACY AND INTERPERSONAL COMMUNICATION ON PUBLIC SPEAKING ANXIETY IN KUALA 1 PUBLIC HIGH SCHOOL STUDENTS - Twelvdes Sadrak Eire Simanjuntak; Rahmi Lubis; Suryani Hardjo (RADJA PUBLIKA, 2024)
Nowadays, anxiety about speaking in public is a problem for many teenagers, especially students. Public speaking anxiety is certainly influenced by many factors. This research aims to analyze and see the influence between self-efficacy and interpersonal communication and public speaking anxiety. This research is included in causal associative quantitative research. The sample for this research was 298 students from SMA N 1 Kuala. Research data was collected using a research scale that was declared valid and reliable. The data analysis technique uses multiple linear regression analysis. The research results show that (1) The self-efficacy variable has a significant influence on public speaking anxiety which has a negative value, because based on the results of the t test, a significant level of 0.002 <0.05 is obtained. And the calculated t value > t table in One-Tailed, namely 10.152 > 2.05. With a coefficient value of 0.571, it means that if self-efficacy is within one unit, it will cause a decrease in students' public speaking anxiety. (2) The interpersonal communication variable in public has a significant influence on public speaking anxiety and has a positive value. Based on the results of the t test, a significant level of 0.03 < 0.05 was obtained and the calculated t value > t table was 2.125 > 2.05 in the Two-Tailed test. With a coefficient value of 0.404, it means that if interpersonal communication increases by one unit, it will lead to a decrease in students' public speaking anxiety. (3) Self-efficacy and interpersonal communication variables have a significant influence simultaneously on public speaking anxiety. Based on the results of the f test, a significance value of 0.000 < 0.05 was obtained and the calculated f value was 74.719 > f table of 4,013. So this proves that simultaneously the three independent variables have a significant influence on students' public speaking anxiety.